Jew - Baker, Cynthia M. (New Brunswick, New Jersey : Rutgers University Press, 2017)
"Jew. The word possesses an uncanny power to provoke and unsettle. For millennia, Jew has signified the consummate Other, a persistent fly in the ointment of grand Western cultural projects and narratives. Jew has not long served, however, as a name for self. With these insights as a point of departure, this book offers a wide-ranging exploration of the key word Jew - a term that lies not only at the heart of Jewish experience and Jewish studies, but, indeed, at the heart of Western civilization as a whole. Beginning with an examination of scholarly debates about the origins and early meanings of Jew, the book unpacks categories like "ethnicity," "race," and "religion" that inevitably feature in attempts to define the word. It goes on to explore the complex challenges that attend the modern appropriation of Jew as a term of self-identification, with forays into Yiddish language and culture, academic scholarship on "the Jew," and meditations on Jew-as-identity by contemporary public intellectuals. Finally, by tracing the phrase new Jews through a range of contexts - including the early Zionist movement, current debates about Muslim immigration to Europe, and recent sociological studies in the U.S. - the book provides a glimpse of what Jew is coming to mean in an era of Internet cultures, genetic sequencing, precarious nationalisms, and proliferating identities"--
Part I. Terms of debate. first Jews -- a Jew outward or a Jew inward? -- Jews, women, slaves -- From ethnos to ethnicity/race and religion -- Part II. State of the (Jew[ish]) question -- Vos macht a yid? -- Jew in Jewish studies -- Thinking (with) Jew(s) -- Part III. In a new key: new Jews -- Zionism's new Jew and the birth of the genomic Jew -- New Jews in a new Europe -- New Jews: a view from the new world.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed December 14, 2016).
eBooks on EBSCOhost
Keywords: Jews -- Identity; Antisemitism; Juifs -- Identité.; Antisémitisme.; antisemitism; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; HISTORY -- World; Antisemitism; Jews -- Identity; Electronic books